Kinematics and kinesthesia of competitive swimmers during dolphin kick swimming in an indoor pool and a water flume - Shimojo, H.; Sengoku, Y.; Tsubakimoto, S.; Takagi, H. (Japan Journal of Physical Education, Health and Sport Sciences, 2014)
This study clarified the differences between swimming performance in a water flume and in a pool by comparing kinematics and kinesthesia during dolphin kick swimming in both conditions. Seven national-level male college swimmers (age 20.4±1.5 years, height 1.73±0.06 m, weight 68.1±6.0 kg) swam using prone dolphin kicks in a water flume channel and in an indoor pool. The target speed was set at 95% of maximum effort. In the pool, we controlled swimming speed by using metronome sounds to change the swimmers' kicking frequency gradually. For data collection, seven anatomical landmarks were marked on the swimmers' bodies using active LED lights. We obtained kinematic data on the swimmers' motion using two-dimensional direct linear transformation (2D-DLT) and investigated their kinesthesia by administering a questionnaire. Although swimming speed (p=.73) and kicking frequency (p=.45) showed no significant difference under both conditions, kicking amplitude was significantly greater in the flume (33.09±2.80% @height) than in the pool (30.45±2.01% @height, p<.05). The kinesthesia questionnaires revealed that the swimmers paid more attention to somatic sense (pool: 9.71±3.50 points, flume: 12.29±3.35 points, p<.05) and vision (pool: 1.14±0.38 points, flume: 2.14±1.21 points, p=.06) in the flume than in the pool. These results suggest that swimmers adapt their motion and kinesthetic awareness purposefully because the water flume presents different conditions. Researchers and coaches should be aware of these differences when they use the water flume.